Evaluasi kesesuaian jenis dan penataan tanaman pada lansekap jalan di Jalan Dharma Giri Gianyar - Krisnayana, Ida Bagus; Utami, Ni Wayan Febriana; Mayun, Ida Ayu (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020, 2020)
Street infrastructure is now equipped with various kinds of plant elements that known as streetscape, so the existence of the street is not monotonous. Beside the landscape of the street also has a function as a medium for green open space. Therefore, the selection of plant species and arrangement of plants in streetscape must be in accordance with the criteria of plant morphology of the streetscape. Evaluation was carried out based on the problems that occur in the suitability of species and arrangement of plants in the landscape of the street. The purpose of this study was to determine the existing conditions found on the streetscape on the Dharma Giri and to determine the suitability of species and arrangement of plants as a streetscape plant. The method used in this research was field survey with a qualitative approach. The results showed that the general condition of the vegetation and plant selection in Dharma Giri streetscape was almost in accordance with the growing conditions needed by the plants. It conditions generally grow well. Mostly the plants were planted in the median part of the street and also in both side of the street which was also able to adapt with direct sunlight exposure and was not require high intensity of watering. It was also observed from the aspect of arrangement using the approach of the three principles of design which includes themes, rhythm, and balance. However, the plant maintenance activities needs to be improved so it possibly maintained  the esthetics and function of the streetscape.